Maternal and Perinatal Outcomes Associated With Extremely High Values for the sFlt‐1 (Soluble fms‐Like Tyrosine Kinase 1)/PlGF (Placental Growth Factor) Ratio. Issue 7 (9th April 2020) - Villalaín, Cecilia; Herraiz, Ignacio; Valle, Leonor; Mendoza, Manel; Delgado, Juan Luis; Vázquez‐Fernández, María; Martínez‐Uriarte, Juan; Melchor, Íñigo; Caamiña, Sara; Fernández‐Oliva, Antoni; Villar, Olga Patricia; Galindo, Alberto
Abstract : Background: There is little knowledge about the significance of extremely high values (>655) for the ratio of sFlt‐1 (soluble fms‐like tyrosine kinase 1) to PlGF (placental growth factor). We aim to describe the time‐to‐delivery interval and maternal and perinatal outcomes when such values are demonstrated while assessing suspected or confirmed placental dysfunction based on clinical or sonographic criteria. Methods and Results: A multicenter retrospective cohort study was performed on 237 singleton gestations between 20+0 and 37+0 weeks included at the time of first demonstrating a sFlt‐1/PlGF ratio >655. Clinicians were aware of this result, but standard protocols were followed for delivery indication. Main outcomes were compared for women with and without preeclampsia at inclusion. In those with preeclampsia (n=185, of whom 77.3% had fetal growth restriction), severe preeclampsia features and fetal growth restriction in stages III or IV were present in 49.2% and 13.5% cases, respectively, at inclusion and in 77.3% and 28.6% cases, respectively, at delivery. In the group without preeclampsia (n=52, 82.7% had fetal growth restriction), these figures were 0% and 30.8%, respectively, at inclusion and 21.2% and 50%, respectively, at delivery. Interestingly, 28% of women without initial preeclampsia developed it later. The median time to delivery was 4 days (interquartile range: 1–6 days) and 7 days (interquartile range: 3–12 days), respectively ( P <0.01). Overall, perinatal mortality was 62.1% before 24 weeks; severe morbidity surpassed 50% before 29 weeks but became absent from 34 weeks. Maternal serious morbidity was high at any gestational age. Conclusions: An sFlt‐1/PlGF ratio >655 is almost invariably associated with preeclampsia or fetal growth restriction that progresses rapidly. In our tertiary care settings, we observed that maternal adverse outcomes were high throughout gestation, whereas perinatal adverse outcomes diminished as pregnancy advanced.